Omission of axillary dissection following nodal downstaging with neoadjuvant chemotherapy - Montagna, Giacomo; Mrdutt, Mary M.; Sun, Susie X.; Hlavin, Callie; Diego, Emilia J.; Wong, Stephanie M.; Barrio, Andrea V.; van den Bruele, Astrid Botty; Cabioglu, Neslihan; Sevilimedu, Varadan; Rosenberger, Laura H.; Hwang, E. Shelley; et al. (JAMA oncology, 2024)
Data on oncological outcomes after omission of axillary lymph node dissection (ALND) in patients with breast cancer that downstages from node positive to negative with neoadjuvant chemotherapy are sparse. Additionally, the best axillary surgical staging technique in this scenario is unknown.To investigate oncological outcomes after sentinel lymph node biopsy (SLNB) with dual-tracer mapping or targeted axillary dissection (TAD), which combines SLNB with localization and retrieval of the clipped lymph node.In this multicenter retrospective cohort study that was conducted at 25 centers in 11 countries, 1144 patients with consecutive stage II to III biopsy-proven node-positive breast cancer were included between April 2013 and December 2020. The cumulative incidence rates of axillary, locoregional, and any invasive (locoregional or distant) recurrence were determined by competing risk analysis.Omission of ALND after SLNB or TAD.The primary end points were the 3-year and 5-year rates of any axillary recurrence. Secondary end points included locoregional recurrence, any invasive (locoregional and distant) recurrence, and the number of lymph nodes removed.A total of 1144 patients (median [IQR] age, 50 [41-59] years; 78 [6.8%] Asian, 105 [9.2%] Black, 102 [8.9%] Hispanic, and 816 [71.0%] White individuals; 666 SLNB [58.2%] and 478 TAD [41.8%]) were included. A total of 1060 patients (93%) had N1 disease, 619 (54%) had ERBB2 (formerly HER2)-positive illness, and 758 (66%) had a breast pathologic complete response. TAD patients were more likely to receive nodal radiation therapy (85% vs 78%; P = .01). The clipped node was successfully retrieved in 97% of TAD cases and 86% of SLNB cases (without localization). The mean (SD) number of sentinel lymph nodes retrieved was 3 (2) vs 4 (2) (P < .001), and the mean (SD) number of total lymph nodes removed was 3.95 (1.97) vs 4.44 (2.04) (P < .001) in the TAD and SLNB groups, respectively. The 5-year rates of any axillary, locoregional, and any invasive recurrence in the entire cohort were 1.0% (95% CI, 0.49%-2.0%), 2.7% (95% CI, 1.6%-4.1%), and 10% (95% CI, 8.3%-13%), respectively. The 3-year cumulative incidence of axillary recurrence did not differ between TAD and SLNB (0.5% vs 0.8%; P = .55).The results of this cohort study showed that axillary recurrence was rare in this setting and was not significantly lower after TAD vs SLNB. These results support omission of ALND in this population.